Pengaruh Dimensi Kualitas Pelayanan Dan Nilai Islami Terhadap Minat Anggota Menggunakan Simpanan Haji Dan Umroh - Habibah, Rizki; Fahrullah, (Jurnal Ekonomika dan Bisnis Islam, 2020)
The high interest of the people of Indonesia to carry out hajj has resulted in a large number of persons who use these conditions to seek profits in an illegal way. Therefore this study aims to determine whether there is an influence between the dimensions and Islamic values on the interests of members using Hajj and Umrah savings. This research is a quantitative study using a descriptive approach that is measured with a Likert scale and analyzed by SPSS version 20 application. The results show that the dimensions of service quality and Islamic values have a relationship with the interests of members using Hajj and Umrah savings.